Methodology of Cross-Cultural Description of Speech Behaviour:A Case Study of INVITATION in German and Russian Discourse; GEMA Online® Journal of Language Studies; Vol. 21, No. 1 - Kotorova E. G. Elizaveta Georgievna (2021, 2021)
Title screen